2001
DOI: 10.1007/s002340000451
|View full text |Cite
|
Sign up to set email alerts
|

Primary brain lymphoma presenting as Parkinson's disease

Abstract: Neoplasm is an uncommon cause of a parkinsonian syndrome. We report a woman with primary brain B-cell lymphoma presenting as Parkinson's disease. After 1 year of the illness, CT and MRI showed lesions without mass effect in the basal ganglia and corpus callosum. The patient did not respond to levodopa and right cerebellar and brain-stem signs appeared, which prompted further neuroimaging, showing an increase in size of the lesions and a right cerebellar and pontine mass. Stereotactic biopsy of the basal gangli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 0 publications
0
16
1
Order By: Relevance
“…Movement disorders as an initial presentation of primary cerebral lymphoma are rare [2][3][4]6]. Previous reports included a 66-year-old woman who presented with left arm chorea, followed by hemifacial dystonic spasms and torticollis and dystonia in the contralateral arm [2], and patients who presented with parkinsonism [3,4,6]. However, our patient is unique as she had reversible isolated choreoathethosis and, unlike the previous report [2], the caudate nuclei were not involved.…”
Section: Discussioncontrasting
confidence: 40%
See 2 more Smart Citations
“…Movement disorders as an initial presentation of primary cerebral lymphoma are rare [2][3][4]6]. Previous reports included a 66-year-old woman who presented with left arm chorea, followed by hemifacial dystonic spasms and torticollis and dystonia in the contralateral arm [2], and patients who presented with parkinsonism [3,4,6]. However, our patient is unique as she had reversible isolated choreoathethosis and, unlike the previous report [2], the caudate nuclei were not involved.…”
Section: Discussioncontrasting
confidence: 40%
“…Presumed paraneoplastic choreic movements in non-Hodgkin's lymphoma have been highlighted [5]. Movement disorders as an initial presentation of primary cerebral lymphoma are rare [2][3][4]6]. Previous reports included a 66-year-old woman who presented with left arm chorea, followed by hemifacial dystonic spasms and torticollis and dystonia in the contralateral arm [2], and patients who presented with parkinsonism [3,4,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sciarra and Sprofkin (1953) reported that 2.1% of patients with Parkinsonism had cerebral tumors and Tolosa and Vilato (1965) reported a frequency of 1%. Most of tumors which result in Parkinsonism involve the basal ganglia (Pramstaller et al 1999), supplementary motor area (Haussermann et al 2001), corpus callousm (Sánchez-Guerra et al 2001), or frontal lobe (Bucciarelli and Cavaliere 1991;Krauss et al 1995). Lesions in the infratentorial compartment have only been reported sporadically in the literature (Pohle and Krauss 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Parkinsonism is an insidious cranial degenerative process with symptoms characterized tremor at rest, rigidity, akinesia/bradykinesia, and postural instability (TRAP), and symptoms can appear individually or in combination (Sánchez-Guerra et al 2001). Etiology varies, but all result in reduction or interference of the level of dopamine in extra-pyramidal pathways.…”
mentioning
confidence: 99%